Empowering Women in the Digital Age : Leveraging AI for Economic Inclusion and Advancement - Saivasan, Rangapriya; Lokhande, Madhavi (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : Gender equality and inclusive economic growth enable women to have control over resources, employment, and entrepreneurship. This has the potential to encourage involvement and have a good economic impact. In light of the changing environment, this study investigated how artificial intelligence (AI) may support the objective of women’s empowerment. Research Methodology : The research methodology for this study was secondary research, specifically thematic analysis and observational study. A wide range of sources, including academic journals, books, research reports, and reputable online platforms, were analyzed alongside analysis of AI-based women empowerment initiatives undertaken across various economies. Findings : The results showed that hiring and employment practices may be made less restrictive by utilizing AI, which would improve the representation of women in traditionally male-dominated fields. Modern technology has also made it simpler to identify and address gender pay disparities, ensuring equitable remuneration. Virtual assistants with AI capabilities have made financial services more accessible to women, enabling them to make well-informed financial decisions and strategic investments. The study highlighted how AI benefits women’s health by enhancing healthcare outcomes with precise diagnosis and practical telemedicine solutions. Practical Implications : This study has implications for policymakers, advocates for women’s rights, AI developers, and gender equality campaigners. Economic empowerment programs, technological innovation, and policy frameworks that are focused on women can all benefit from these ideas. Economic success can be reconfigured for a future focused on growth by optimizing women’s potential equity. Originality Value : This study has original insights into the intersection of gender disparities, AI accessibility, and empowerment, informing strategies for inclusive development.